Training Media Accessibility Professionals: An Employability and Knowledge Transfer Experience - Enríquez-Aranda, Mercedes; García-Luque, Francisca (My University, 2023)
As part of the university’s commitment to the student’s career guidance within the European Higher Education Area, the University of Malaga promotes curricular training actions, which are not considered “isolated elements, but a structural part of the university education” (Universidad de Málaga, 2021), in order to improve employability in relation to knowledge transfer. Employability is understood as a quality criterion for universities (Jiménez Vivas, 2009), but also as a constant challenge (Navarro Brotons & Cuadrado Rey, 2019). In Translation Studies some exploratory works on this professional competence (Galán Mañas, 2017; Álvarez Álvarez, 2020) have been successfully developed. During the academic year 2021-2022, the project “The professional practice of media accessibility in television” was carried out, framed within the modules in Audiovisual Translation of the Degree in Translation and Interpreting. The project focused on showing the students the professional processes of media accessibility on the television channel by means of two actions: a guided field visit to the television studios in Malaga and a professional seminar given online by a company specialized in audiovisual accessibility. The research tools used to assess the students’ feedback on the experience were two satisfaction questionnaires, each for one action. The questionnaires were divided into two different parts, one allowing a quantitative analysis (closed questions) and the other a qualitative one (open questions). The discussion of the results boosts the academic reflection on the convenience of continuing with similar projects in the future, so that students can experience first-hand the work context in which their future work would take place and acquire knowledge about the professional processes of media accessibility (workflow, project management, hiring...).
References Álvarez Álvarez, S. (2020). Empleabilidad y emprendimiento en la formación de traductores e intérpretes: nuevas competencias, nuevas estrategias. In S. Álvarez Álvarez & M. T. Ortego Antón (Ed.): Perfiles estratégicos de traductores e intérpretes. La transmisión de la información experta multilingüe en la sociedad del conocimiento del siglo XXI (pp. 43-68). Comares. Galán Mañas, A. (2017). Programa para la mejora de la empleabilidad de los egresados en Traducción e Interpretación. Un estudio de caso. Conexão Letras, 12(17), 153-171. Jiménez Vivas, Amparo (2009). Reflexiones sobre la necesidad de acercamiento entre universidad y mercado laboral. Revista Iberoamericana de Educación, 50(1). http://rieoei.org/deloslectores/2895Vivas.pdf Navarro Brotons, L. & A. Cuadrado Rey (2019). La inserción laboral de los egresados del Máster en Traducción Institucional: la importancia de las prácticas externas. In R. Roig-Vila (Ed.): Investigación e Innovación en la Enseñanza Superior. Nuevos contextos, nuevas ideas (pp. 815-824). Octaedro. Universidad de Málaga. (2021). Convocatoria de acciones de la línea 7, Acción 731 del I Plan Propio Integral de Docencia de la Universidad de Málaga. Convocatoria 2022. Acción sectorial 731 – Formación curricular para la mejora de la empleabilidad y/o del emprendimiento. https://www.uma.es/secretariageneral/newsecgen/images/boletin/20211119_52433.pdf
Keywords: Traducción - Congresos; Accesibilidad; media accessibility; translator’s training; employability; knowledge transfer